Implementation of the first respiratory syncytial (RSV) immunization campaign with nirsevimab in an autonomous community in Spain - Jaime Jesús Pérez Martín; Matilde Zornoza Moreno (Taylor & Francis Group, 2024)
Respiratory syncytial virus (RSV) is the main cause of low respiratory tract infections in infants under one year of age. In the 2023/2024 season, the monoclonal antibody nirsevimab was available to protect children from RSV, and Spain has become one of the first countries worldwide to implement this strategy. It is essential to evaluate the results of this first campaign and different characteristics of the immunized population in order to plan next campaigns, especially for countries that are going to include this immunization. Our coverage was high (91.5% for those born during the season and 88.3% globally). For those born during the season, only 4.9% preferred not to immunize at the maternity hospital, which meant an average delay of 27.45 days. We observed a lower coverage in the population of immigrant origin. There was a rapid pace of immunization, since for those born before the beginning of the campaign the mean to be immunized was 15.63 days, without differences between healthy and at-risk children. This allows immunization before the RSV season (90% of the catch-up children had been immunized on November 3). The average age at which all the immunized children have received nirsevimab was lower in healthy children compared to those with risk conditions (49.65 versus 232.85 days). For those born during the campaign, the average age was also lower in healthy children (3.14 versus 14.58 days). In conclusion, we consider that the implementation of the immunization strategy with nirsevimab in the Region of Murcia, Spain, has been a success.